Development of microsatellite loci in Artocarpus altilis (Moraceae) and cross‐amplification in congeneric species1. (21st June 2013) - Witherup, Colby; Ragone, Diane; Wiesner‐Hanks, Tyr; Irish, Brian; Scheffler, Brian; Simpson, Sheron; Zee, Francis; Zuberi, M. Iqbal; Zerega, Nyree J. C.
Abstract : Premise of the study: Microsatellite loci were isolated and characterized from enriched genomic libraries of Artocarpus altilis (breadfruit) and tested in four Artocarpus species and one hybrid. The microsatellite markers provide new tools for further studies in Artocarpus . Methods and Results: A total of 25 microsatellite loci were evaluated across four Artocarpus species and one hybrid. Twenty‐one microsatellite loci were evaluated on A. altilis (241), A. camansi (34), A. mariannensis (15), and A. altilis × mariannensis (64) samples. Nine of those loci plus four additional loci were evaluated on A. heterophyllus (jackfruit, 426) samples. All loci are polymorphic for at least one species. The average number of alleles ranges from two to nine within taxa. Conclusions: These microsatellite primers will facilitate further studies on the genetic structure and evolutionary and domestication history of Artocarpus species. They will aid in cultivar identification and establishing germplasm conservation strategies for breadfruit and jackfruit.